Estudio y diseño del plan estratégico para el ahorro de energía aplicando metodología dmaic six sigma en Cervecería Nacional - Molina Ramirez, Luis Fernando (2013)
The National Brewery study aims developed in electricity savings using the implementation of the Six Sigma DMAIC methodology. Energy efficiency is defined as the act of getting the most out of the electricity consumed and facilities needed for the generation, transport and use, ensuring interference-free operation of all receivers connected to the distribution network, this will should study first electric energy consuming systems. Through studies of equipment and other factors that generate waste in electricity consumption, with the results achieved to take the respective actions to minimize the impact on CO2 emissions, making the most of the electricity consumed. Within the project implementation process standards in the handling of equipment, training and supervision was an implemented specialist for members belonging to the company, for good management teams, generating better ideas and willingness to change.